2007
DOI: 10.1111/j.1440-1754.2007.01172.x
|View full text |Cite
|
Sign up to set email alerts
|

Trans fatty acids from milk of Brazilian mothers of premature infants

Abstract: The study showed that the intake of TFA occupies an intermediate position between the values of North America and European countries, reflecting the ongoing transition to industrialised foods in Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 41 publications
2
19
1
1
Order By: Relevance
“…In our study, the breast milk ratio of LA to ALA was 23 to 1, which might explain the higher AA levels. This is in agreement with observations of variable ratios of LA to ALA in colostrum from mothers of preterm and full-term infants 18 . Excess LA downregulates ALA metabolism into its LCPUFA because it competes with ALA for desaturation 24 .…”
Section: Commentsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, the breast milk ratio of LA to ALA was 23 to 1, which might explain the higher AA levels. This is in agreement with observations of variable ratios of LA to ALA in colostrum from mothers of preterm and full-term infants 18 . Excess LA downregulates ALA metabolism into its LCPUFA because it competes with ALA for desaturation 24 .…”
Section: Commentsupporting
confidence: 93%
“…We found that breast milk from the first week postpartum contained an elevated ratio of LA to ALA that was positively associated with measures of receptive language. Our study found similar percentages of LCPUFA in the milk from mothers of preterm infants to a previous study conducted in Brazil 18 and higher values compared to other studies in different countries 19 . Specifically, the values of AA in the present study (0.4%) were slightly above the worldwide mean value of 0.32% (SD 0.22) 20 .…”
Section: Commentsupporting
confidence: 87%
“…Fatty acids were separated using an SP 2560 capillary column (Supelco, USA), with 100 m × 0.25 mm × 0.20 μm measurements. The chromatographic conditions were similar to those described by Tinoco et al [55]. The esters were identified by comparing their retention times to known standards (Sigma, Supelco).…”
Section: Methodsmentioning
confidence: 99%
“…Fatty acids were separated using an SP 2560 capillary column (Supelco, USA), with 100 m × 0.25 mm × 0.20  μ m measurements. The chromatographic conditions were similar to those described by Tinoco et al [23]. The methylated fatty acids were identified by comparing their retention times to known standards (Nu-Chek Prep.…”
Section: Methodsmentioning
confidence: 99%